Clinical advantages of robot‐assisted partial nephrectomy versus laparoscopic partial nephrectomy in terms of global and split renal functions: A propensity score‐matched comparative analysis. (3rd March 2021) - Kobayashi, Satoshi; Mutaguchi, Jun; Kashiwagi, Eiji; Takeuchi, Ario; Shiota, Masaki; Inokuchi, Junichi; Eto, Masatoshi
Abstract : Objectives: To identify predictors of renal function preservation, and to compare the global and split renal function outcomes of robot‐assisted partial nephrectomy and laparoscopic partial nephrectomy. Methods: Demographic, operative and pathological data, as well as renal function outcomes, of 251 patients who underwent laparoscopic ( n = 104) and robot‐assisted ( n = 147) partial nephrectomy between 2008 and 2018 were retrospectively analyzed. Propensity score matching (1:1) was carried out to adjust for potential baseline confounders. Functional outcomes were assessed based on the estimated glomerular filtration rate and dynamic renal scintigraphy (using 99m Tc‐mercaptoacetyltriglycine), including renal volumetric analysis. Results: A total of 98 patients were allocated to each partial nephrectomy group. Ischemic (laparoscopic vs robot‐assisted partial nephrectomy: 29 vs 15 min, P < 0.001) and operative times (181 vs 100 min, P < 0.001) were shorter in robot‐assisted partial nephrectomy. The preservation ratio of global renal function at 3 months (88.3% vs 91.4%, P = 0.040) and 12 months (87.8% vs 91.5%, P = 0.010) postoperatively, and the renal function of the operated kidney (80.3% vs 88.2%, P < 0.001) were greater after robot‐assisted partial nephrectomy. In robot‐assisted partial nephrectomy, the volume of resected parenchyma was significantly smaller (27.2 vs 15.5 mL, P < 0.001), resulting in greater postoperative normal parenchymal volumes (120 vs 132 mL, P < 0.001) and a greater parenchymal preservation ratio (81.1% vs 90.1%, P < 0.001). The parenchymal preservation ratio was the strongest predictor of renal function preservation after surgery ( P < 0.001, odds ratio 6.02). Conclusions: Robot‐assisted partial nephrectomy allows better preservation of split renal function than laparoscopic partial nephrectomy by increasing the parenchymal preservation ratio. This translates into better postoperative global renal function.